EFFECT OF TOPICAL BRIMONIDINE ON NMDA RECEPTOR EXPRESSION AND RETINA GANGLION CELL DENSITY IN TRAUMATIC OPTIC NEUROPATHY RATS MODEL: Oral Presentation - Experimental Study - Resident - RR. WIDYASTUTI PASPARINI; Riski Prihatningtias; Arief Wildan; Hermawan Istiadi (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Traumatic optic neuropathy is a visual disturbance caused by acute injury to the optic nerve which results in retinal ganglion cell apoptosis through the glutamate excitotoxicity pathway. Brimonidine is an alpha 2-receptor agonist that acts as a neuroprotector in the glutamate excitotoxicity pathway and causes modulation of NMDA receptors associated with glutamate. Objective of this study is to prove the effect of topical brimonidine on NMDA receptor expression and retinal ganglion cell density in a rat model of traumatic optic neuropathy Methods : Rat models of traumatic optic neuropathy was carried out using the optic nerve crush method. The treatment group was given topical brimonidine 0.15% 1 drop/12 hours for 14 days. NMDA receptor expression was assessed by immunohistochemical staining and retinal ganglion cell density was assessed by Hematoxylin-eosin staining. Statistical analysis was performed to assess the correlation between NMDA receptor expression and retinal ganglion cell density Results : The Allred score of NMDA receptors expression in the treatment group was lower than control group, with significant difference (p=0.002). The mean density of retinal ganglion cells in the treatment and control group was 20,99  7,76 and 12,51  3,10, respectively with a significant difference (p=0.032). There was a significant correlation between NMDA receptor expression and retinal ganglion cell density in the treatment group (p=0.035) with strong negative correlation (r= -0.611) Conclusion : Topical administration of brimonidine to the Wistar rat model of traumatic optic neuropathy can suppress NMDA receptor expression and maintain retinal cell ganglion density